Gardners' lives in the long C19th - Denby, J (2023)
The lives of domestic gardeners during Hobsbawm’s long C19th, 1789-1914 are examined. The scope of the thesis is those parts of gardeners’ lives which are relevant to themes in economic and social history, such as education, remuneration, housing, inventions innovation and discovery rather than the gardeners’ daily activities and routines. The importance of gardens and gardening in the economic, social and cultural life of the C19th is established through an analysis of political and literary sources. As part of the domestic domain gardens were under the control of women, who were also concerned in their design and development